EFFECT OF ACETONE SOLUBLE AND ACETONE INSOLUBLE FRACTIONS OF ALLIUM CEPA ON SOME ANIMAL MODELS OF ASTHMA (International Journal of Ayurveda and Pharma Research, 2020)
Current Asthma therapy lack satisfactory effect due to various adverse effects, hence patients are moving to Ayurveda. Researchers conducted studies in last decades on plants mentioned in Ayurveda used for asthama has shown Anti-asthamic, Anti-histaminic and Anti-allergic activity. Present study is conducted to study the anti-asthmatic activity of acetone soluble and insoluble extract of Allium cepa.In this process dried peels of Allium cepa were immersed in 95% ethanol for 48hr and the extract obtained was further fractionated with anhydrous acetone to get acetone soluble (ASF) and acetone insoluble (AIF) fractions. Effect of the fractions was studied on isolated goat tracheal chain suspended in Kreb’s solution and percentage contractile response was measured. Albino Swiss mice (22-25g) of either sex were subjected to milk- induced leucocytosis and eosinophilia to study adaptogenic and anti-allergic activity respectively. Effects of both the extracts were also studied on clonidine-induced catalepsy and clonidine induced mast cell degranulation in mice as a measure of central and peripheral mast cell stabilization respectively. Wistar rats (150-180g) were used to study effect of fractions on passive paw anaphylaxis to study immunomodulatory and anti-inflammatory activity.